Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Sometimes it’s possible to use induction backwards, proving things from n

to n − 1 instead of vice-versa! For instance, consider the statement


x1 + · · · + xn n
 
P (n) : x1 · · · xn ≤ , if x1 , · · · , xn ≥ 0.
n
This is true when n = 2, since (x1 + x2 )2 − 4x1 x2 = (x1 − x2 )2 ≥ 0.
a. By setting xn = (x1 +· · ·+xn−1 )/(n−1), prove that P (n) implies P (n−1)
whenever n > 1.
Proof: By the induction hypothesis P (n), we have
x1 + · · · + xn n
 
x1 · · · xn ≤
n
Dividing both sides by xn , we obtain
1 x1 + · · · + xn n
 
x1 · · · xn−1 ≤
xn n
x1 + · · · + xn−1 x1 + · · · + xn−1 n
 
n−1
= +
x1 + · · · + xn−1 n n(n − 1)
 n
n−1 1 1
= (n − 1)(x1 + · · · + xn−1 ) +
n n(n − 1)
 n
n−1 n−1 1
= (x 1 + · · · + x n−1 ) 1 +
nn n−1
  n
n−1 n
= n
(x1 + · · · + xn−1 )n−1
n n−1
x1 + · · · + xn−1 n−1
 
= .
n−1
Thus we have shown that P (n) implies P (n − 1). 

1
2

b. Show that P (n) and P (2) imply P (2n).


Proof: We have
x1 · · · x2n = (x1 · · · xn )(xn+1 · · · x2n )
x1 + · · · + xn n  xn+1 · · · x2n n
 

n n
xn+1 · · · x2n  n
  
x1 + · · · + xn
=
n n
1 x1 + · · · + xn xn+1 + · · · + x2n 2n
  
≤ +
2 n n
 2n
x1 + · · · + x2n
= .
2n
Thus we see that P (n) and P (2) imply P (2n). 
c. Explain why this implies the truth of P (n) for all n.
Proof: Since P (n) and P (2) imply P (2n) for every positive integer n and
we already proved the base case, P (2), this implies P (2k ) for every positive
integer k. But since P (n) also implies P (n − 1) for every integer n > 1, we
have P (n) for every positive integer n ≤ 2k for every positive integer k. But
since k can be arbitrarily large, this implies P (n) for all n. 

You might also like